Impacts of hippotherapy simulation on balance, postural control, and spasticity of thigh adductor muscles in children with spastic bilateral Cerebral Palsy: A single-blind clinical trial study - Ramezani, Kiana; kalantari , minoo; pashmdarfard, marzieh; Akbarzadeh Baghban, Alireza; Rahmanian , Sara; Khavari, Ghodrat (Iranian Journal of Child Neurology, 2025)
Objectives Cerebral Palsy (CP) is a group of movement disorders. A recently proposed occupational therapy approach to reduce spasticity and improve balance and postural control is Hippotherapy Simulation (HS). The present study attempts to investigate how HS impacts balance, postural control, and spasticity of adductor muscles in children with spastic bilateral CP. Materials & Methods Thirty-one children with bilateral spastic CP, five to nine years old, were selected via availability sampling and divided into the intervention group (n=16) and the control (n=15) through stratified block randomization. Assessment tools, including Pediatric Balance Scale (PBS), Trunk Control Measurement Scale (TCMS), Modified Ashworth Scale (MAS), Gross Motor Function Measure (GMFM), Pediatric Evaluation of Disability Inventory (PEDI), and goniometry, were completed by an assessor unaware of the children’s grouping. Results After the intervention, the average total scores of all variables in the HS group significantly exceeded those in the control group (P<0.01). However, no significant differences were observed between the groups at follow-up, underlining the necessity of providing long-term or recurrent interventions to maintain improvements in gross motor function. This approach also constructively influenced postural control and mitigated the spasticity of adductor thigh muscles. Conclusion This study showed the multimodal effect of simulated hippotherapy combined with occupational therapy routine exercises on the physical performance of children with bilateral spastic CP.